1992
DOI: 10.1111/j.1540-8159.1992.tb02991.x
|View full text |Cite
|
Sign up to set email alerts
|

VDD Single Pass Lead Pacing; Sustained Pacemaker Mediated Tachycardias Unrelated to Retrograde Atrial Activation

Abstract: Pacemaker mediated tachycardias (PMTs) are a well known complication of P synchronous pacing. Although the initiating mechanisms are several, all of them are associated with retrograde atrial activation, which is sensed by the atrial sensing channel, resulting in ventricular pacing. In 19 patients suffering from symptomatic AV conduction disturbances and normal sinus node function, a VDD pacing system connected to a single pass ventricular lead with dual chamber electrodes was implanted. The bipolar atrial ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Disorders of pacemaker function due to sensing of the QRS through atrial leads have long been recognized [3][4][5][6] . This phenomenon is classically described in atrial single chamber pacemakers, and leads to P wave undersensing, to inappropriate decrease in the pacing rate in AAI or AAIR mode or to pacemaker-mediated tachycardia in AAT mode [6,7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disorders of pacemaker function due to sensing of the QRS through atrial leads have long been recognized [3][4][5][6] . This phenomenon is classically described in atrial single chamber pacemakers, and leads to P wave undersensing, to inappropriate decrease in the pacing rate in AAI or AAIR mode or to pacemaker-mediated tachycardia in AAT mode [6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…These problems are more rarely encountered in modern dual chamber pacemakers, because of the atrial blanking and refractory periods automatically added after each ventricular spontaneous or paced event and because of the common use of bipolar atrial leads [6] . Anecdotal cases of pacemaker mediated tachycardias have been reported when the timing of inappropriate detection is sufficiently delayed [3,4,5,7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single lead VDD pacemakers are more suseptible to FFELT because a very high atrial sensitivity is required to sense the small atrial signals registered by the floating atrial electrode. 12…”
Section: Discussionmentioning
confidence: 99%
“…To prevent pacemaker induced complications, an appropriate patient selection is important, confirming no history of supraventricular tachycardia, atrial flutter, or atrial fibrillation. However, several reports (7,8) have demonstrated that supraventricular tachycardia sometimes develops after implantation and requires a change to VVI pacing. Brownlee at al.…”
Section: Discussionmentioning
confidence: 99%